A general free cash flow theory of capital structure - Buus, Tomáš (Journal of Business Economics and Management, 2014)
This paper provides general framework for handling time-varying cost of capital, leverage, tax rates, and capital values in a dynamic free cash flow theory of capital structure. That enables efficient analysis of the recent competing theories of capital structure. After including the costs of financial distress and risk premium of debt in the cash flow model, this paper provides a new look at cost of tax shield from the point of view of risk-return relationship. Cost of tax shield is not constant, but depends on leverage and is mostly between cost of assets and cost of debt. Moreover the simulation of firm value and capital structure in presence of taxes, risk, and growth shows that unique optimal leverages exist for each combination of the above factors. The risk-enhanced cash flow theory can explain both the observations, which support pecking order theory, free cash flow theory and tradeoff theory of capital structure. Moreover it fits some evidence, which resists these theories: highly leveraged low growth companies and moderately leveraged large profitable companies.